KEPUASAN PELANGGAN PENGGUNA JASA SIM CARD: (Studi pada Generasi Milenial Penguna Jasa Simcard Tri yang Beraktifitas di Gandaria Utara) - Muhammad Bukhari, (2020)
This research is a quantitative study that aims to determine the effect of price, product quality and service quality on customer satisfaction. The population in this study was Tri simcard customers in North Gandaria. The sample size was taken as many as 75 respondents, with a non-probability sampling method with a purposive sampling method. Data collection was carried out through questionnaires. The analysis technique used is the PLS (Partial Least Square) analysis method with SmartPLS3.0 software. The results of this study indicate that (1) Price has a positive and significant effect on customer satisfaction with a path coefficient of 0.487. (2) product quality has a negative and not significant effect on customer satisfaction with a path coefficient of -0.077. (3) Service quality has a positive and significant effect on customer satisfaction with a path coefficient of 0.678